1990
DOI: 10.1002/pd.1970100509
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome mosaicism not detected at amniocentesis

Abstract: Amniocentesis was performed because of a fetal abdominal wall defect, and a 45,X karyotype was obtained. A near-normal male infant with no features of Turner syndrome was delivered. The karyotype of the infant was 45,X/46,X,dic(Y)(q11), with each of the cell lines present in approximately 50 per cent of the lymphocytes and fibroblasts examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…Prenatal karyotype from amniocentesis showed that 100 per cent of the cells were abnormal and that fetal blood cells were 100 per cent normal. A similar discrepancy has been described recently in which sex chromosome mosaicism was not detected at amniocentesis as described by Roland et al (1990).…”
Section: Discussionsupporting
confidence: 83%
“…Prenatal karyotype from amniocentesis showed that 100 per cent of the cells were abnormal and that fetal blood cells were 100 per cent normal. A similar discrepancy has been described recently in which sex chromosome mosaicism was not detected at amniocentesis as described by Roland et al (1990).…”
Section: Discussionsupporting
confidence: 83%
“…Such problems of specificity have been reported only sporadically 26 27. Although placental mosaicism is a well recognised problem in the use of chorion villus sampling,28 29 30 31 32 this cannot explain the findings concerning amniocentesis.…”
Section: Discussionmentioning
confidence: 99%